The Elephant in the Room. On the Relation of Demographic Change, Public Services and Civic Engagement in Germany - Nadler, Robert (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
In Germany’s territorial planning community, the relation of demographic change, the provision of public services and civic engagement is mainly sketched out as a substitution logic, in which volunteer work substitutes for employed work of state agencies in the provision of public services. The aim of this paper is a critical assessment of this substitution logic. The central question is: how realistic is this fictional model of substitution in the light of current patterns of demographic change in Germany? Methodologically the paper draws on a literature review, which is, first, used to outline definitions and empirical evidence regarding civic engagement in Germany, and second, to present in detail and critically reflect the main discourse in German territorial planning regarding the relation of public services and demographic change. The central result is the description of three dilemmas (geographic, political and motivational dilemma), that hinder a realistic implementation of substitution. As a consequence, suggestions are made for a better conceptualization of the relation of public service provision and civic engagement in the light of demographic change. It is argued that civic engagement should more strongly be conceived in combination with tools for recognition, the geographic disparities of civic engagement must be considered more strongly, and state agents must reflect on and redefine their role and self-conception in relation to engaging social groups, with the aim of a more equal partnership.